A Luting Technique for Passive Fit of Implant‐Supported Fixed Dentures. Issue 1 (21st April 2015) - Menini, Maria; Dellepiane, Elena; Pera, Paolo; Bevilacqua, Marco; Pesce, Paolo; Pera, Francesco; Tealdo, Tiziano
Abstract: Several factors contribute to distortion of implant prostheses during fabrication and could prevent passive, accurate adaptation between implants and implant frameworks. The misfit between implants and restorative components may be significant and possibly lead to biologic or mechanical complications. The aim of this article is to describe a laboratory luting technique used to lute implant cylinders to metal frameworks in implant prostheses. This technique provides accurate, passive fits. According to this technique, titanium implant cylinders provided with corresponding external castable cylinders are used. Implant cylinders are screwed into the analogs in the master cast while the castable cylinders on top are splinted together using castable resin to realize a castable resin pattern. After casting, the framework is adjusted and cemented to the titanium cylinders on the master cast. Due to its ease and quickness of use and clinical efficiencies, this technique is deemed particularly useful in immediate loading rehabilitations.